Analisis Tingkat Kepercayaan Diri dan Tingkat Kecemasan pada Atlet Renang saat Bertanding Krapprov JATENG 2025 - Ajenia Dona Novita; Aziz Amrulloh (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to determine the levels of self-confidence and anxiety of swimming athletes during the Central Java InterClub Swimming Championship (Krapprov) 2025. This research employed a descriptive quantitative approach using a survey design. The participants consisted of 30 swimming athletes who competed in the Central Java Krapprov, selected through total sampling. Data were collected using self-confidence and anxiety questionnaires adapted from previous studies. Data analysis was conducted using descriptive statistics, including minimum and maximum scores, mean, standard deviation, frequency, and percentage, with the assistance of IBM SPSS Statistics version 25.0. The results revealed that the athletes’ self-confidence level was predominantly categorized as low (40.01%), with a mean score of 111.17 and a standard deviation of 11.507. Meanwhile, the level of anxiety was mainly categorized as moderate (50.00%), with a mean score of 18.27 and a standard deviation of 5.638. These findings indicate that although most athletes experienced moderate anxiety, low selfconfidence remains the primary psychological challenge that may affect athletic performance during competition.